The Inhibitory Effect of 6-Gingerol on Ubiquitin-Specific Peptidase 14 Enhances Autophagy-Dependent Ferroptosis and Anti-Tumor in vivo and in vitro - Tsai, Yun; Xia, Changbo; Sun, Zhongwen (Frontiers in Pharmacology, 2020)
Lung cancer is the most common malignant tumor and is the leading cause of cancer-related deaths worldwide. Extraction of bioactive substances from herbs is considered as an alternative method to traditional treatment. 6-Gingerol is a naturally occurring phenol found in ginger that can be used to treat tumors and suppress inflammation. To determine whether 6-Gingerol can be used as a therapeutic agent for tumors. In this study, tumor-bearing mice were used as an animal model and A549 as a cell model. Western blot was used to detect the expression of autophagy related proteins ubiquitin-specific peptidase 14 (USP14), Beclin1, microtubule-associated protein light chain 3 (LC3) and ferroptosis related proteins nuclear receptor coactivator 4 (NCOA4), ferritin heavy chain 1 (FTH1), transferrin receptor 1 (TfR1), glutathione peroxidase 4 (GPX4), activating transcription factor4 (ATF4) in vivo and in vitro. MTT and EdU were used to detect the viability of A549 cells. H&E and immunofluorescence were used to localize and detect the expression of proteins. The detection of ROS was performed using fluorescence probes. It was found that the administration of 6-Gingerol decreased the expression of USP14, greatly increased the number of autophagosomes, reactive oxygen species (ROS) and iron concentration, decreased the survival and proliferation rate of A549 cells, and significantly decreased tumor volume and weight. The results indicate that 6-Gingerol inhibits lung cancer cell growth via suppression of USP14 expression and its downstream regulation of autophagy-dependent ferroptosis, revealing the function and efficacy of 6-Gingerol as a therapeutic compound in A549 and its possible mechanism of action.